Optimization of Electrical Energy Data Monitoring System Management in Smart Home System for Electrical Switches Using Extreme Programming Method - Hendy Indrawan Sunardi; Aidil Saputra Kirsan; Muhammad Hafidh Ma’ruf; Irma Fitria (Jurnal Teknik Elektro dan Komputer TRIAC, 2025)
Technological advances are currently increasing rapidly, this development cannot be denied that it can provide convenience to humans in their daily lives, one of which can be through the implementation of a smart home system based on the Internet of Things (IoT). In this study, the implementation will implement a real-time monitoring and control system for electricity usage through an IoT-based electrical switch to be able to implement a smart home system based on the Internet of Things. In previous studies, the system has been successfully implemented but still has limitations such as the electrical energy monitoring system only displays data for one month, the size of the device is less efficient, and still has instability of the electric current given to the microcontroller. Therefore, this study aims to optimize the smart home system on an IoT-based electrical switch so that it can be used more efficiently and flexibly. Development of a website-based system so that it can be used flexibly. This study uses the Extreme Programming (XP) method because this method is considered suitable for this development because it provides dynamic and flexible needs in change. This research is expected to provide increased efficiency, flexibility, and responsiveness so that it can reduce energy waste and provide convenience for users in managing electricity consumption effectively.